Gold Nanorod Bioconjugates for Active Tumor Targeting and Photothermal Therapy - Hadiyah N. Green; Dmitry V. Martyshkin; Cynthia M. Rodenburg; Eben L. Rosenthal; Sergey B. Mirov (Journal of Nanotechnology)
The mastery of active tumor targeting is a great challenge in near infrared photothermal therapy (NIRPTT). To improve efficiency for targeted treatment of malignant tumors, we modify the technique of conjugating gold nanoparticles to tumor-specific antibodies. Polyethylene glycol-coated (PEGylated) gold nanorods (GNRs) were fabricated and conjugated to an anti-EGFR antibody. We characterized the conjugation efficiency of the GNRs by comparing the efficiency of antibody binding and the photothermal effect of the GNRs before and after conjugation. We demonstrate that the binding efficiency of the antibodies conjugated to the PEGylated GNRs is comparable to the binding efficiency of the unmodified antibodies and 33.9% greater than PEGylated antibody-GNR conjugates as reported by Liao and Hafner (2005). In addition, cell death by NIRPTT was sufficient to kill nearly 90% of tumor cells, which is comparable to NIRPTT with GNRs alone confirming that NIRPTT using GNRs is not compromised by conjugation of GNRs to antibodies.